ETERNAL PEACE PROJECTS IN THE LATE MIDDLE AGES (Heritage, 2020)
Projects on the establishment of world peace in the late Middle Ages were initially marked by religious views on the world. Christian church was the subject of war and peace and it did not make differences among peoples. It had universal aspirations. This dogmatic comprehension will be abandoned by the appearance of national states where the state becomes subject of war and peace. A division among nations appears and the possibility of their mutual recognition. In that way relations among states are being regulated from the point of view of international relations. His basic principle becomes the one of sovereign equality, this could happen after the termination of religious wars which got its peak by Westphalia peace,Starting from Dubois, Podjebrady, Penn, Duke of Silly, via Hobbes, Grotius end Puffendorf, it will be possible to determine how changes in society political systems and way of production influenced the developments of ideas on perpetual peace. The achievements of these thinkers were revolutionary and were still valid. It is worth mentioning the principles of sovereign equality of states, the presence of realism in international relations and the existence of judicial institutions such as the International Court of Justice.
Keywords: Perpetual peace, war, church, state, international law, absolute monarchy